Pengaruh Dosis Kompos dan Interval Penyiangan Terhadap Keragaman Gulma Pada Tanaman Jagung Ketan Lokal Sumbawa (Zea Mays Ceratina) Di Lahan Salin - Kusnayadi, Heri; Sumiyanti, Sumiyanti; Kusumawardani, Wening (Universitas Medan Area, 2021)
This study aims to determine the effect of a combination of biological compost and intervals of weeding on weed diversity in the cultivation of local sticky rice maize in Sumbawa in saline land. To determine the effect of giving biological compost on weed diversity in the cultivation of local sticky rice maize in Sumbawa on saline land. To determine the effect of weeding intervals on weed diversity on the cultivation of local Sumbawa glutinous maize in saline land. The research was conducted in Baru Tahan Village, North Moyo District, Sumbawa Regency, West Nusa Tenggara (NTB) and was carried star March to May 2020. The method used was an experimental method. The experimental design used was a factorial randomized block design (RBD) with 2 factors, namely Biological Compost (A) and Weed Interval (B). With 6 treatments and 3 replications in order to obtain 18 experimental plots. The data from the observations were analyzed using analysis of variance (Anova) at a significant level of 5%. The results showed that the effect of single treatment and combination of biological compost dosage and weeding interval were not significantly different in all parameters of weed diversity observation.